Effect of two-stage sintering on phase formation, microstructure and dielectric properties of perovskite PMN ceramics derived from a corundum Mg4Nb2O9 precursor - R. Wongmaneerung (2018)
Pure and dense relaxor perovskite ceramics of lead magnesium niobate (PMN) have been successfully fabricated by using a combination between a corundum Mg4Nb2O9 B-site precursor and a two-stage sintering techniques. Effect of doubly sintering on phase formation, microstructure and dielectric properties of the PMN ceramics was determined via XRD, SEM and dielectric measurement. It has been found that under suitable two-stage sintering schemes, dense and pure perovskite PMN ceramics derived from a corundum B-site precursor route can be successfully achieved with better dielectric properties than those of ceramics from either a conventional or a two-stage sintered columbite B-site precursor methods. © 2008 Elsevier B.V. All rights reserved.